DASAMUKA PEJAH SEBAGAI IDE PENCIPTAAN KARYA SENI LUKIS - Yuda Junaedi; Agus Cahyana; Anis Sudjana (ATRAT: Jurnal Seni Rupa, 2024)
This study highlights the importance of examining the tragic and romantic expressions of Dasamuka, the antagonist character in Ramayana paintings, as a reflection of Indonesian culture from a contemporary perspective. These artworks serve as a means to understand the complexity of human nature within the context of Indonesia’s rich historical and cultural heritage. The research employs an indirect method with specific stages, including material selection, visual sketches of Dasamuka, choosing object interactions, and selecting narrative backdrops with glimpses of tragic stage elements, expressive movements, lighting techniques, and finishing touches. The result is a painting that portrays the tragic and romantic expressions of Dasamuka, honing the artist’s ability to create unique and expressive works while preserving Indonesian cultural values. By placing the antagonist character at the center of discussion, this Ramayana painting offers a new dimension to the classic tale and invites the audience to realize that each character has their own story and reasons. Through this artwork, Indonesian society, especially the younger generation, is reminded of the importance of preserving cultural identity and local wisdom values. Moreover, this artwork serves as a means to strengthen and preserve Indonesia’s cultural identity amidst the rapid waves of globalization. Keywords: Dasamuka, Ramayana, paintings, Indonesian culture. --------------------------------------------------------------------- Kajian ini menyoroti pentingnya mengkaji ekspresi tragis dan romantis Dasamuka, tokoh antagonis lukisan Ramayana, sebagai cerminan budaya Indonesia dari perspektif kontemporer. Karya seni ini merupakan cara untuk memahami kompleksitas sifat manusia dalam konteks sejarah dan budaya Indonesia yang kaya akan warisan tradisi.Metode penelitian adalah metode tidak langsung dengan langkah-langkah pemilihan material, sketsa visual Dasamuka, interaksi objek dan pemilihan tetap naratif dengan kilasan tragedi panggung, gerakan ekspresif, teknik lighting dan finishing. Hasilnya adalah lukisan yang menghadirkan ekspresi tragis dan romantis Dasamuka, mengasah kemampuan seniman dalam menciptakan lukisan yang unik dan ekspresif, serta melestarikan nilai-nilai budaya Indonesia. Dengan menjadikan tokoh antagonis sebagai pusat perbincangan, lukisan Ramayana ini menawarkan dimensi baru pada cerita klasik dan mengajak penonton untuk menyadari bahwa setiap tokoh memiliki cerita dan alasannya masing-masing. Melalui karya seni ini, masyarakat Indonesia khususnya generasi muda diingatkan akan pentingnya menjaga identitas budaya dan nilai-nilai kearifan lokal. Selain itu, karya seni ini menjadi sarana untuk memperkuat dan melestarikan identitas budaya Indonesia di tengah derasnya arus globalisasi. Kata kunci: Dasamuka, Ramayana, seni lukis, budaya Indonesia